Neurexin and neuroligins jointly regulate synaptic degeneration at the Drosophila neuromuscular junction based on TEM studies - Guangming, Gan; Mei, Chen; Qinfeng, Yu; Xiang, Gao; Chenchen, Zhang; Qingyuan, Sheng; Wei, Xie; Junhua, Geng (Frontiers in Cellular Neuroscience, 2023)
The Drosophila larval neuromuscular junction (NMJ) is a well-known model system and is often used to study synapse development. Here, we show synaptic degeneration at NMJ boutons, primarily based on transmission electron microscopy (TEM) studies.When degeneration starts, the subsynaptic reticulum (SSR) swells, retracts and folds inward, and the residual SSR then degenerates into a disordered, thin or linear membrane. The axon terminal begins to degenerate from the central region, and the Tbar detaches from the presynaptic membrane with clustered synaptic vesicles to accelerate large-scale degeneration. There are two degeneration modes for clear synaptic vesicles. In the first mode, synaptic vesicles without actin filaments degenerate on the membrane with ultrafine spots and collapse and disperse to form an irregular profile with dark ultrafine particles. In the second mode, clear synaptic vesicles with actin filaments degenerate into dense synaptic vesicles, form irregular dark clumps without a membrane, and collapse and disperse to form an irregular profile with dark ultrafine particles. Last, all residual membranes in NMJ boutons degenerate into a linear shape, and all the residual elements in axon terminals degenerate and eventually form a cluster of dark ultrafine particles. Swelling and retraction of the SSR occurs prior to degradation of the axon terminal, which degenerates faster and with more intensity than the SSR. NMJ bouton degeneration occurs under normal physiological conditions but is accelerated in Drosophila neurexin (dnrx) dnrx 273 , Drosophila neuroligin (dnlg) dnlg1 and dnlg4 mutants and dnrx 83 ;dnlg3 and dnlg2;dnlg3 double mutants, which suggests that both neurexin and neuroligins play a vital role in preventing synaptic degeneration.